Determinants of off-balance sheet (OBS) activities: a case of selected retail banks in Malaysia / Nafiu Olaniyi Oladokun, Shamsul Kamariah Abdullah and Charmele Ayadurai. - Oladokun, Nafiu Olaniyi; Abdullah, Shamsul Kamariah; Ayadurai, Charmele (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2019)
The present paper examines factors influencing the Off-Balance Sheet activities of selected commercial banks in Malaysia for the period 2004-2014. OBS activities are an integral part of financial institutions in response to the needs of businesses for different types of guarantee that have conflicting implications on the stability of financial institutions. Data collected on selected banks from the Bankscope database was analyzed using the Generalized Method of Moments (GMM) regression. Specifically, the study built its analysis on three main recognized determining factors namely: (1) liquidity motives, (2) credit risk transfer motive, (3) profitability motives, and (4) capital arbitrage motive. The findings thus suggest that the selected banks mainly used OBS instruments for capital arbitrage purpose, enhancing operational efficiency and managing loan portfolio risks. The findings further suggested that its usage for capital arbitrage purposes may undermine the regulatory measures of accurately estimating and monitoring the risk of banks. The findings thus offer significant practical and policy implications that can help to enhance financial stability.